Stereotypes about Old Age, Social Support, Aging Anxiety and Evaluations of One's Own Health (2016)
As the aging population in Colombia grows, caring for older adults falls not just to family but also to the community including friends and religious organizations. While there is very little research on ageism in Colombia, it is increasingly urgent to understand the role of social support of the growing older population. Two studies were conducted with a community sample in Bogotá, Colombia. In a pilot study, we developed a measure of positive and negative stereotyping of older adults. In the main study with participants aged between 54 and 83, we explored the relations among endorsement of positive and negative stereotypes, anxiety about aging, perceived and expected physical and mental health, and expectations of social support. We found that perceived lack of social support and negative stereotyping significantly predict more anxiety towards aging, while positive evaluations of one's own mental health predict less anxiety. Surprisingly, greater expectations of social support predict more aging anxiety. In turn, aging anxiety and positive stereotyping predicted evaluations of mental (but not physical) health. Additionally, poorer evaluations of physical health, aging anxiety and negative stereotyping (though only marginally) significantly predict greater expectations of social support. Implications of the findings are discussed. © 2016 The Society for the Psychological Study of Social Issues.